Effect of Yogic Ocular Exercises on Convergence Insufficiency - Shahid, Sharmeen; Muhammad Haris; Shafqat, Zainab; Ejaz, Faiza (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Objective: To assess the effect of yogic ocular exercises on convergence insufficiency Methodology: A quasi-experimental study was conducted at the University of Lahore Teaching Hospital from July -August 2025. Forty-seven participants (31 females, 16 males) aged 18–26 years with convergence insufficiency were recruited after taking approval from the IRB committee UOL/IREB/25/0009. RAF ruler was used to measure near point of convergence (NPC) at baseline, three weeks, and six weeks. Participants performed a set of yogic ocular exercises (palming, blinking, sideways viewing, rotational viewing, diagonal viewing, nose-tip gazing, near-distant viewing, concentrated gazing, candle flame viewing, acupressure stimulation) for 30 minutes daily over six weeks. Data were analyzed using Friedman and Wilcoxon signed-rank tests.